2017
DOI: 10.1016/j.amsu.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

A survey of doctors at a UK teaching hospital to assess understanding of recent changes to consent law

Abstract: BackgroundThe UK Supreme Court recently ruled that when consenting patients for treatments or procedures, clinicians must also discuss any associated material risks. We surveyed medical staff at a large UK teaching hospital in order to ascertain knowledge of consent law and current understanding of this change.Materials and methodsEmail survey sent to medical staff in all specialities at Norfolk and Norwich University Hospital in February 2016.Results245 responses (141 Consultants and 104 junior doctors, respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Montgomery is viewed as a landmark case in consent practice, it triggered intense professional debate, so it was encouraging that most of the HCPS were aware of it. Additionally, contrary to the findings of O'Brien et al 21 all the obstetricians in this study were familiar with the details of the case. By contrast, however, their midwifery colleagues had limited knowledge.…”
Section: Main Findingscontrasting
confidence: 99%
“…Montgomery is viewed as a landmark case in consent practice, it triggered intense professional debate, so it was encouraging that most of the HCPS were aware of it. Additionally, contrary to the findings of O'Brien et al 21 all the obstetricians in this study were familiar with the details of the case. By contrast, however, their midwifery colleagues had limited knowledge.…”
Section: Main Findingscontrasting
confidence: 99%
“…They found that the majority of responding doctors were not familiar with their current medicolegal requirements with respect to material risk. 6 Approximately two-thirds of respondents were not aware, or were only vaguely aware, of pertinent legal cases that had recently redefined a doctor's legal requirements for consent. 6 Currently in Australia, there is a paucity of evidence regarding practising doctors' understanding of consent in medical law and their awareness of the medicolegal cases that have shaped it.…”
Section: Introductionmentioning
confidence: 99%
“…6 Approximately two-thirds of respondents were not aware, or were only vaguely aware, of pertinent legal cases that had recently redefined a doctor's legal requirements for consent. 6 Currently in Australia, there is a paucity of evidence regarding practising doctors' understanding of consent in medical law and their awareness of the medicolegal cases that have shaped it. Rogers v Whitaker (1992) is one of the most pertinent medicolegal cases in Australia; however, it is now 27 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, O'Brien argues that the GMC guidance was actually shaped by legal cases questioning Bolam from the mid‐1990s. He argues that when the 2008 GMC guidance ‘explicitly called for a patient‐centred approach’, it was ‘reflecting the process of departure from Bolam started by Chester v Afshar and Pearce ’ 55 . In his view, it is clinical practice that has been slow to catch up with legal paradigm shifts on risk disclosure and patient consent.…”
Section: Resultsmentioning
confidence: 99%